Ivermectin: An Anthelmintic, an Insecticide, and Much More. Issue 1 (January 2021) - Martin, Richard J.; Robertson, Alan P.; Choudhary, Shivani
Abstract : Here we tell the story of ivermectin, describing its anthelmintic and insecticidal actions and recent studies that have sought to reposition ivermectin for the treatment of other diseases that are not caused by helminth and insect parasites. The standard theory of its anthelmintic and insecticidal mode of action is that it is a selective positive allosteric modulator of glutamate-gated chloride channels found in nematodes and insects. At higher concentrations, ivermectin also acts as an allosteric modulator of ion channels found in host central nervous systems. In addition, in tissue culture, at concentrations higher than anthelmintic concentrations, ivermectin shows antiviral, antimalarial, antimetabolic, and anticancer effects. Caution is required before extrapolating from these preliminary repositioning experiments to clinical use, particularly for Covid-19 treatment, because of the high concentrations of ivermectin used in tissue-culture experiments. Highlights: Ivermectin and analogs are remarkable broad-spectrum anthelmintics and insecticides, but resistance is now a real concern. Resistance mechanisms have been proposed but they do not appear to account for the resistance seen in parasitic nematodes. Ivermectin is very effective for controlling microfilaria at low doses but it has limited effects on adult filaria for unclear reasons. Ivermectin is a positive allosteric modulator of glutamate-gated chloride channels found in both nematodes and insects, and it binds to the channels in their lipid phase. Ivermectin and analogs also modulate other ion channels and have effects on the mammalian host brain when the blood–brain barrier is impaired. Preliminary repositioning studies of ivermectin show antiviral, antimalarial, antimetabolic, and anticancer effects at concentrations higher than anthelmintic concentrations in tissue culture.